URGENSI ADMINISTRASI PENDIDIKAN DALAM DUNIA PENDIDIKAN - Saputra, Alan Lutfi Gesang (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2022)
Education administration is the part of education in charge of providing assistance, direction and assistance to achieve a goal. Therefore, a person who handles education administration must really understand how to organize, manage and archive all things that are visible (hardfile) and invisible (softfile). This cannot be separated from the role of all people who master the field of education administration with the administration of Education, of course, teaching and learning activities in educational institutions can run smoothly.so education administration can be said to be one of the things that support the success of teaching and learning activities. Then explained some points related to education administration, namely: understanding of education administration, objectives, benefits and functions of Education Administration, characteristics of Education Administration, kinds of Education Administration and the scope of Education Admission